Meningkatkan Keterampilan Pukulan Forehand dalam Permainan Tenis Meja Melalui Pantulan Bola Ke Dinding pada Siswa Kelas VIIIa SMP Negeri 15 Palu - Afiyati L. Djuru; Tri Murtono; Andi Saparia; Muhammad Agusman; Delvi Kristanti Liloi (Jurnal Porkes, 2026)
This study was motivated by the low level of table tennis forehand skills among eighth-grade students in Class VIIIa at SMP Negeri 15 Palu, as well as the limited sports facilities and equipment at the school. The purpose of this study was to determine and analyze the effect of wall-bounce drills on improving forehand skills in table tennis among eighth-grade students in Class VIIIa at SMP Negeri 15 Palu. This study employed an experimental method using a one-group pre-test post-test design. The population and sample consisted of 25 eighth-grade students in Class VIIIa at SMP Negeri 15 Palu. The training intervention was conducted over four weeks, with three sessions per week. Data were collected using a forehand stroke skill test (backboard test). Data analysis employed a dependent t-test with a significance level of 5%. The results showed an increase in the average score from 5.60 at the pre-test to 9.36 at the post-test, representing a 67.14% improvement. The t-test results showed that the calculated t-value (31.86) was greater than the critical t-value (1.711) at a 5% significance level with 24 degrees of freedom, and the p-value was 0.000 < 0.05; therefore, H₀ was rejected and H₁ was accepted. The conclusion of this study is that wall-bounce drills have a significant effect on improving the forehand stroke skills of eighth-grade students in Class VIIIa at SMP Negeri 15 Palu.